Anisotropic adhesive gel and preparation method and application thereof
By designing an array of 2D adhesion strips with alternately arranged adhesive strips and non-adhesive strips, the strength and preparation problems of anisotropic adhesion gels under high aspect ratio and inclined 3D micro-column structures in the prior art are solved, and long-term stable, friction-resistant anisotropic adhesion performance is achieved, which is suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202510012440.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing anisotropic adhesion gel requires extremely high body strength and strict preparation methods under the characteristics of high aspect ratio and inclined 3D micro-column structure, which limits the large-area preparation and application of materials, and the 3D micro-nano structure is prone to structural collapse and leads to interface bond failure.
An array of 2D adhesion strips with alternately arranged adhesive strips and non-adhesion strips are designed, and the adhesion strips are formed by interface self-assembly and polymerized, and the non-adhesion strips are anchored in a specific area through interactions to achieve the anisotropic adhesion properties of the adhesion gel.
It achieves long-term, stable, friction-resistant anisotropic adhesion performance, simplifies the preparation process, reduces strict restrictions on material processing, and is suitable for flexible adhesion grippers, smart wearable devices and wall-climbing robots.
Smart Images

Figure CN119391335B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functionalized gels. More specifically, it relates to an anisotropic adhesive gel, its preparation method, and its applications. Background Technology
[0002] Anisotropy refers to the fact that all or part of the chemical, physical, and other properties of a substance change with the change of direction, exhibiting different properties in different directions. For example, CN114989470A discloses a humidity-responsive anisotropic composite surface. This composite surface can have obvious soft / hard morphological transformation under different humidity levels and has both anisotropic and isotropic structural switching, thereby achieving controllable adhesion of the surface to objects and other properties, thus enabling controllable adhesion of the objects to be adhered to.
[0003] In recent years, the construction of patterns on gel surfaces to achieve excellent anisotropic adhesion has attracted widespread attention. Single-component gel materials, due to the homogeneity of their bulk phase and surface properties, cannot achieve effective anisotropic adhesion. Currently, many studies focus on constructing gecko-like 3D ciliary structures on gel surfaces to achieve anisotropic adhesion. However, for existing surface-patterned adhesion gels, the structural units of their 3D cilia are typically at the micro-nano scale. These anisotropic adhesion gels, due to their high aspect ratio and tilted 3D micropillars, require extremely high bulk strength and impose strict limitations on material processing methods, severely restricting large-area fabrication and application. Furthermore, the fine 3D micro / nano structures are prone to structural collapse under external forces, leading to interfacial adhesion failure. Therefore, constructing adhesion patterns on gel surfaces in a single step to achieve long-term stable anisotropic adhesion is of great significance. Summary of the Invention
[0004] Based on this, the first objective of this invention is to provide an anisotropic adhesive gel. This adhesive gel has alternating adhesive and non-adhesive strips, wherein the adhesive strips exhibit high adhesion and high friction, while the non-adhesive strips exhibit low adhesion and low friction. This structural and performance difference design allows the adhesive gel to exhibit anisotropic adhesive properties overall. This research not only greatly simplifies the complex and cumbersome steps involved in constructing 3D micro / nano structures in the traditional preparation of anisotropic adhesive materials, but also achieves long-lasting, stable, and friction-resistant anisotropic adhesive properties.
[0005] A second objective of this invention is to provide a method for preparing the adhesive gel as described above.
[0006] A third objective of this invention is to provide an application of the adhesive gel described above in the preparation of flexible adhesive grippers, smart wearable devices, and wall-climbing robots.
[0007] To achieve the first objective mentioned above, the present invention adopts the following technical solution:
[0008] This invention discloses an anisotropic adhesive gel, wherein the adhesive gel is a 2D adhesive strip array composed of alternating adhesive strips and non-adhesive strips;
[0009] The adhesive strip is obtained by interfacial self-assembly and polymerization of a prepolymer rich in adhesive gel monomers in a patterned region modified with n-octyltriethoxysilane.
[0010] The non-adhesive strips are obtained by interfacial self-assembly and polymerization of a prepolymer rich in non-adhesive gel monomers in a patterned region modified with hydroxyl groups.
[0011] Inspired by the unique arc-shaped adhesive sheet structure and excellent anisotropic adhesion behavior of gecko feet, the adhesive strip array is designed as alternating arc-shaped or pointed strips. The arc-shaped strips include adhesive arc-shaped strips and non-adhesive arc-shaped strips, while the pointed strips include adhesive pointed strips and non-adhesive pointed strips. This design enables the adhesive gel to achieve anisotropic adhesion; that is, the peeling force required when peeling from the pointed tip or arc-shaped apex of the adhesive strip is much greater than the force required when peeling from the arms of the pointed strip or the arms of the arc-shaped strip. Similarly, the frictional force exhibited when sliding from the arc-shaped apex or pointed tip of the adhesive strip towards its arms is much greater than the frictional force when sliding from the arms of the arc-shaped strip or the arms of the pointed strip towards the arc-shaped apex or pointed tip. Furthermore, by adjusting the width, curvature, and angle of the arc-shaped or pointed strips, precise control of the anisotropic peeling force and frictional force can be achieved.
[0012] Furthermore, the adhesive gel monomer is selected from one or more of isooctyl acrylate, dodecyl methacrylate, n-butyl acrylate, dopamine octyl acrylate, and oleic acid methacrylate;
[0013] The non-adhesive gel monomer is selected from one or more of acrylamide, hydroxyethyl methacrylate, hydroxyethyl acrylate, N,N-dimethylacrylamide, methacrylamide, and N-isopropylacrylamide.
[0014] Furthermore, the adhesive strip and the non-adhesive strip are respectively in the shape of an arc-shaped strip or a pointed strip. The adhesive strip and the non-adhesive strip have the same shape and their openings face the same direction. That is, the adhesive strip and the non-adhesive strip can both be arc-shaped strips or both be pointed strips.
[0015] The width of each adhesive strip and each non-adhesive strip is 10µm-1.0cm, which allows for precise control of the width from the micrometer scale to the centimeter scale.
[0016] The adhesive strip and the non-adhesive strip are arc-shaped strips with an arc range of 45-180°, such as 45°, 60°, 90°, 135°, etc.
[0017] The adhesive and non-adhesive strips are angular strips with an angle range of 45-135°, such as 45°, 60°, 90°, 135°, etc., which can achieve large-scale control of the arc or angle.
[0018] Furthermore, the adhesive strip and the non-adhesive strip are in the shape of pointed strips. The peel strength of peeling from the pointed tip of the adhesive strip is greater than the peel strength of peeling from the two arms of the pointed strip. The sliding friction from the pointed tip of the adhesive strip to the two arms of the pointed strip is greater than the sliding friction from the two arms of the pointed strip to the pointed tip.
[0019] Furthermore, the adhesive strip and the non-adhesive strip are in the shape of pointed strips. The peeling force from the pointed tip of the adhesive strip is 1.3-4.0 times that from the two arms of the pointed strip, and the sliding friction from the pointed tip of the adhesive strip to the two arms of the pointed strip is 1.2-3.0 times that from the two arms of the pointed strip to the pointed tip.
[0020] Furthermore, the adhesive strip and the non-adhesive strip are arc-shaped strips. The peel strength from the arc-shaped top of the adhesive strip is greater than the peel strength from the arc-shaped arms. The sliding friction from the arc-shaped top of the adhesive strip to the arc-shaped arms is greater than the sliding friction from the arc-shaped arms to the arc-shaped top.
[0021] Furthermore, the adhesive strip and the non-adhesive strip are arc-shaped strips. The peeling force from the arc-shaped top of the adhesive strip is 1.2-5.0 times that from the arc-shaped arms, and the sliding friction from the arc-shaped top of the adhesive strip to the arc-shaped arms is 1.2-3.0 times that from the arc-shaped arms to the arc-shaped top.
[0022] To achieve the second objective mentioned above, the present invention adopts the following technical solution:
[0023] This invention discloses a method for preparing the adhesive gel as described above, comprising the following steps:
[0024] 1) Preparation of patterned substrate
[0025] The substrate is subjected to plasma treatment and n-octyltriethoxysilane modification treatment according to the predetermined adhesion strip array pattern to obtain a patterned substrate with alternating modified regions.
[0026] 2) Prepare prepolymer solutions rich in adhesive gel monomers and prepolymer solutions rich in non-adhesive gel monomers.
[0027] The adhesion gel monomer, the first crosslinking agent and the first photoinitiator are mixed to obtain a prepolymer solution rich in adhesion gel monomer;
[0028] The non-adhesive gel monomer, the second crosslinking agent, and the second photoinitiator are mixed in water to obtain a prepolymer solution rich in non-adhesive gel monomer.
[0029] 3) Preparation of adhesion gel
[0030] A prepolymer solution rich in adhesive gel monomers and a prepolymer solution rich in non-adhesive gel monomers are mixed to obtain a mixed prepolymer solution. 0.05-0.2g of emulsifier is added per 10g of mixed prepolymer solution. The emulsified solution is applied to a patterned substrate. The adhesive gel monomers and non-adhesive gel monomers complete the self-assembly and polymerization process on the patterned substrate to obtain an adhesive gel.
[0031] In this invention, the inductive effect of hydrophilic / hydrophobic interactions at the solid / liquid interface is utilized to cause non-adhesive gel monomers and adhesive gel monomers to move directionally at the interface. The non-adhesive gel monomers are anchored to the plasma-treated substrate region through hydrophilic interactions, while the adhesive gel monomers are anchored to the substrate region modified with n-octyltriethoxysilane through hydrophobic interactions. After a one-step photopolymerization, the wettability pattern on the substrate surface can be perfectly transferred to the gel surface, thereby obtaining the designed adhesive strip array.
[0032] Furthermore, the molar ratio of the adhesive gel monomer and the non-adhesive gel monomer in the mixed prepolymer liquid is 3:1 to 1:1, and can be 3:1, 2:1 or 1:1, for example.
[0033] Furthermore, in the prepolymer solution rich in adhesive gel monomers, the molar ratio of the adhesive gel monomers, the first crosslinking agent, and the first photoinitiator is 0.05-0.20: 0.0010-0.0025: 0.0001-0.0002.
[0034] In the prepolymer solution rich in non-adhesive gel monomers, the concentration of the non-adhesive gel monomers is 0.5-3.0 mol / L, for example 2.5 mol / L, the content of the second crosslinking agent is 0.05-0.2 mg / mL, for example 0.15 mg / mL, and the content of the second photoinitiator is 0.05-0.2 mg / mL, for example 0.15 mg / mL.
[0035] Furthermore, the first crosslinking agent is selected from one or more of triethylene glycol acrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, and propylene glycol dimethacrylate;
[0036] The first photoinitiator is selected from 2-hydroxy-2-methyl-1-phenylpropanone and / or 1-phenyl-1,2-propanedione-2-acetanilide;
[0037] The second crosslinking agent is selected from N,N-dimethylbisacrylamide and / or N,N'-bis(2-aminoethyl)acrylamide;
[0038] The second photoinitiator is selected from one or more of α-ketoglutaric acid, Irgacure 2959, acetophenone, and benzoylbenzophenone;
[0039] The emulsifier is selected from one or more of polyvinyl alcohol, Tween, sodium lauryl sulfate, and lecithin.
[0040] Furthermore, the polymerization process employs photopolymerization, with a light power of 100-120W and a photopolymerization time of 40-60 minutes.
[0041] Furthermore, in the third step of preparing the adhesive gel, the prepolymer liquid rich in adhesive gel monomers and the prepolymer liquid rich in non-adhesive gel monomers can be applied sequentially to the patterned substrate, or the prepolymer liquid rich in adhesive gel monomers and the prepolymer liquid rich in non-adhesive gel monomers can be mixed evenly before being applied together to the patterned substrate.
[0042] To achieve the third objective mentioned above, the present invention adopts the following technical solution:
[0043] This invention discloses an application of the adhesive gel described above in the preparation of flexible adhesive grippers, smart wearable devices, and wall-climbing robots.
[0044] The beneficial effects of this invention are as follows:
[0045] This invention first uses plasma modification and n-octyltriethoxysilane modification to design a predetermined pattern on the substrate. Then, utilizing the inductive effect of the hydrophilic / hydrophobic interactions at the solid / liquid interface, adhesive gel monomers and non-adhesive gel monomers applied to the patterned substrate undergo directional migration. Non-adhesive gel monomers self-assemble in the hydroxyl-modified patterned substrate region due to hydrophilic interactions, while adhesive gel monomers self-assemble in the n-octyltriethoxysilane-modified patterned substrate region due to hydrophobic interactions. Finally, photoinitiation is used to complete emulsion interfacial polymerization, resulting in an anisotropic adhesive gel with a 2D adhesive strip array. This preparation process is simple and simplifies the complex preparation steps required to construct 3D structures for anisotropic adhesion.
[0046] The anisotropic adhesion ability of the adhesive gel can be controlled by adjusting the emulsion ratio and composition, as well as the width, curvature, and angle of the strips. Studies have shown that in the adhesive gel prepared by this invention, the adhesive and non-adhesive strips are angular in shape. The peeling force from the angular tip of the adhesive strip is 1.3-4.0 times that from the two arms of the angular shape, and the sliding friction from the angular tip to the two arms of the adhesive strip is 1.2-3.0 times that from the arms to the tip. In the adhesive gel prepared by this invention, the adhesive and non-adhesive strips are arc-shaped. The peeling force from the arc-shaped tip of the adhesive strip is 1.2-5.0 times that from the two arms of the arc shape, and the sliding friction from the arc-shaped tip to the two arms of the adhesive strip is 1.2-3.0 times that from the arms to the tip.
[0047] The adhesive gel prepared by this invention can be widely used in flexible adhesive grippers, smart wearable devices, and wall-climbing robots. Attached Figure Description
[0048] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.
[0049] Figure 1 The image shows a physical picture of the adhesive gel prepared in Example 1.
[0050] Figure 2 A schematic diagram of the adhesive gel prepared in Example 2-1 is shown.
[0051] Figure 3 A schematic diagram is shown of the adhesion gels prepared in Examples 2-1 to 2-5 being subjected to a 90° peel force test.
[0052] Figure 4 A schematic diagram is shown showing the tribological properties of the adhesive gels prepared in Examples 4-1 to 4-4.
[0053] Figure 5 Optical images and scanning electron microscope images of the adhesion gels prepared in Examples 4-4 after 1000 rubs are shown.
[0054] Figure 6 A schematic diagram of the adhesive gel prepared in Example 5-2 is shown. Detailed Implementation
[0055] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments and accompanying drawings, further explains the invention. Similar components in the drawings are indicated by the same reference numerals. Those skilled in the art should understand that the specific description below is illustrative rather than restrictive and should not be construed as limiting the scope of protection of the present invention.
[0056] Example 1
[0057] 1) Patterned base
[0058] This invention provides, by way of example, a quartz substrate having alternating hydroxyl-modified bands and silane-modified bands, specifically prepared by the following method steps:
[0059] a. A cleaned quartz sheet with dimensions of 3cm*3cm*1mm is subjected to oxygen plasma treatment for 600s at a power of 300W. After oxygen plasma treatment, the entire surface of the quartz sheet is modified with hydroxyl groups.
[0060] b. Spin-coat the photoresist S1805 onto the surface of the quartz wafer obtained in step a in the yellow light area. The spin-coating speed is 2000 rpm, the acceleration is 500 rpm / s, and the spin-coating time is 30s. Then heat at 110℃ for 30s to cure the photoresist and store it away from light.
[0061] c. Cover the quartz sheet obtained in step b with the designed strip-shaped mask in the yellow light area, and perform a photolithography step. The exposure wavelength is 350nm and the exposure time is 12s. The mask size is 2cm*1cm, and the light-transmitting area and the opaque area are alternating rectangular strips of 1cm*5mm.
[0062] d. Develop the exposed quartz film obtained in step c in a 300 MIF developer solution for 12 seconds. Rinse with deionized water for 12 seconds, dry with N2, and heat at 110°C for 30 seconds to dry for later use. The quartz substrate in the unmasked area of the photomask is exposed, and the masked area is covered with photoresist.
[0063] e. The partially photoresist-covered quartz wafer obtained in step d is subjected to oxygen plasma treatment for 600s at a power of 300W to modify the surface of the partially photoresist-covered quartz wafer with hydroxyl groups. The treated quartz wafer is then placed in a vacuum oven, and 75µL of n-octyltriethoxysilane is added dropwise next to the sample in the oven. The oven door is closed, and the mixture is heated to 80°C for at least 8 hours.
[0064] f. Clean the quartz wafer obtained in step e with ethanol to remove the remaining photoresist, and then dry it with N2 to obtain a patterned substrate with alternating hydroxyl-modified rectangular stripes and silane-modified rectangular stripes.
[0065] 2) Adhesion gel: rectangular strip array
[0066] This invention provides an example of an adhesive gel prepared on the above-described patterned substrate, specifically prepared through the following method steps:
[0067] a. Preparation of non-adhesive gel prepolymer: The non-adhesive gel monomer acrylamide, the photoinitiator α-ketoglutarate, and the crosslinking agent N,N-dimethylbisacrylamide are mixed to obtain a non-adhesive gel prepolymer, wherein water is used as the solvent, the concentration of acrylamide is 2.5 mol / L, the concentration of α-ketoglutarate is 0.15 mg / mL, and the concentration of N,N-dimethylbisacrylamide is 0.15 mg / mL;
[0068] b. Preparation of adhesion gel prepolymer: 0.15 mol of adhesion gel monomer isooctyl acrylate, 0.0015 mol of triethylene glycol acrylate and 0.00015 mol of 2-hydroxy-2-methyl-1-phenylpropanone were mixed and dispersed to obtain adhesion gel prepolymer.
[0069] c. Mix the adhesive gel prepolymer and the non-adhesive gel prepolymer at a molar ratio of 2:1 to obtain a mixed prepolymer. Add 0.1g of emulsifier PVA to every 10g of the mixed prepolymer and emulsify for 20s at 585W to obtain a stable mixed emulsion.
[0070] d. Add 4g of the mixed emulsion dropwise onto the patterned substrate obtained above, and place it in a photochemical reactor filled with N2. The non-adhesive gel monomers and adhesive gel monomers in the mixed emulsion aggregate on the surface of a quartz sheet with alternating hydroxyl-modified and silane-modified bands, respectively. Then, polymerize under UV light at 100W for 40 minutes. Finally, separate the polymerized gel from the quartz sheet, and remove the gel without patterned edges to obtain an anisotropic adhesive gel with alternating adhesive and non-adhesive gel bands on the surface. See the sample image below. Figure 1 The prepared gel surface induced alternating adhesive and non-adhesive rectangular bands, each rectangular band measuring 1 cm x 5 mm. Figure 1 The white area represents the adhesive region, and the blue area represents the non-adhesive region.
[0071] 3) 90° peel force test
[0072] The adhesion test employed a 90° peel force test, and all peel force tests in this invention were conducted using a Mark-10ESM301 testing platform. The test sample size was 2cm × 1cm, with polyimide tape used as a backing material adhered to the back of the test sample to prevent stretching during the test. During the test, one end was clamped with a fixture, and the sample was peeled upwards at a speed of 50 mm / min. The bottom of the testing platform moved at the same speed to ensure a stable 90° peel angle. The maximum value of force / width (width is 1cm) in the resulting displacement-force curve was recorded as the peel force.
[0073] The test results showed that the peel force of the adhesive strip in the adhesive gel prepared in Example 1 was 221.8 ± 36.4 N / m, and the peel force of the non-adhesive strip was 10.2 ± 3.9 N / m.
[0074] Example 2-1
[0075] The patterned substrate preparation process is the same as in Example 1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 10 µm and the arc α is 90°.
[0076] The adhesive gel was prepared in the same manner as in Example 1. A schematic diagram of the prepared adhesive gel can be found in [reference needed]. Figure 2 It has alternating adhesive and non-adhesive arc strips, each with a width of 10 µm and an arc angle α of 90°.
[0077] Example 2-2
[0078] The patterned substrate preparation process is the same as in Example 2-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 100µm and the arc is 90°.
[0079] The adhesive gel was prepared in the same manner as in Example 2-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 100 µm and an arc angle α of 90°.
[0080] Example 2-3
[0081] The patterned substrate preparation process is the same as in Example 2-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 300µm and the arc is 90°.
[0082] The adhesive gel was prepared in the same manner as in Example 2-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 300 µm and an arc angle α of 90°.
[0083] Examples 2-4
[0084] The patterned substrate preparation process is the same as in Example 2-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 1 mm.
[0085] The adhesive gel was prepared in the same manner as in Example 2-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 1 mm and an arc angle α of 90°.
[0086] Examples 2-5
[0087] The patterned substrate preparation process is the same as in Example 2-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 5 mm.
[0088] The adhesive gel was prepared in the same manner as in Example 2-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 5 mm and an arc angle α of 90°.
[0089] The adhesive gels prepared in Examples 2-1 to 2-5 were subjected to a 90° peel force test. The test procedure was the same as in Example 1. A schematic diagram of the peel force test is shown below. Figure 3 The results are shown in Table 1. The peeling force required when peeling from the top of the arc is significantly different from the peeling force required when peeling from the two arms of the arc strip, that is, anisotropic peeling force is achieved, with an anisotropy ratio of 1.4-1.8. This study has potential applications in flexible adhesive grippers, smart wearable devices, and wall-climbing robots.
[0090] Table 1
[0091]
[0092] Example 3-1
[0093] The patterned substrate preparation process is the same as in Example 1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the hydroxyl-modified arc stripes is 300 µm, the width of the silane-modified arc stripes is 300 µm, and the arc is 90°.
[0094] The adhesive gel was prepared in the same manner as in Example 1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 300 µm and an arc angle α of 90°.
[0095] Example 3-2
[0096] The patterned substrate preparation process is the same as in Example 3-1, except that the patterned substrate with alternating hydroxyl-modified arc strips and silane-modified arc strips is obtained by changing the shape of the mask. The width of the hydroxyl-modified arc strips is 1.5 mm, the width of the silane-modified arc strips is 300 µm, and the arc is 90°.
[0097] The adhesive gel was prepared in the same manner as in Example 3-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips. Each non-adhesive arc-shaped strip was 1.5 mm long, and each adhesive arc-shaped strip was 300 µm wide with an arc angle α of 90°.
[0098] Example 3-3
[0099] The patterned substrate preparation process is the same as in Example 3-1, except that the patterned substrate with alternating hydroxyl-modified arc strips and silane-modified arc strips is obtained by changing the shape of the mask. The width of the hydroxyl-modified arc strips is 2.7 mm, the width of the silane-modified arc strips is 300 µm, and the arc is 90°.
[0100] The adhesive gel was prepared in the same manner as in Example 3-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips. Each adhesive non-arc strip was 2.7 mm long, and each adhesive arc-shaped strip was 300 µm wide with an arc angle α of 90°.
[0101] Examples 3-4
[0102] The patterned substrate preparation process is the same as in Example 3-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the hydroxyl-modified arc stripes is 1 cm, the width of the silane-modified arc stripes is 300 µm, and the arc is 90°.
[0103] The adhesive gel was prepared in the same manner as in Example 3-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips. Each non-adhesive arc-shaped strip was 1 cm long, and each adhesive arc-shaped strip was 300 µm wide with an arc angle α of 90°.
[0104] The adhesive gels prepared in Examples 3-1 to 3-4 were subjected to 90° peel force tests, and the results are shown in Table 2. The peel force required when peeling from the top of the arc is significantly different from the peel force required when peeling from the two arms of the arc strip, that is, anisotropic peel force is achieved, with an anisotropy ratio of 1.8-3.0.
[0105] Table 2
[0106]
[0107] Example 4-1
[0108] The patterned substrate preparation process is the same as in Example 1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 300 µm and the arc is 45°.
[0109] The adhesive gel was prepared in the same manner as in Example 1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 300 µm and an arc angle α of 45°.
[0110] Example 4-2
[0111] The patterned substrate preparation process is the same as in Example 4-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 300µm and the arc is 90°.
[0112] The adhesive gel was prepared in the same manner as in Example 4-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 300 µm and an arc angle α of 90°.
[0113] Example 4-3
[0114] The patterned substrate preparation process is the same as in Example 4-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 300µm and the arc is 135°.
[0115] The adhesive gel was prepared in the same manner as in Example 4-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 300 µm and an arc angle α of 135°.
[0116] Example 4-4
[0117] The patterned substrate preparation process is the same as in Example 4-1, except that the patterned substrate with alternating hydroxyl-modified arc stripes and silane-modified arc stripes is obtained by changing the shape of the mask. The width of the arc stripes is 300µm and the arc is 180°.
[0118] The adhesive gel was prepared in the same manner as in Example 4-1, but it had alternating adhesive arc-shaped strips and non-adhesive arc-shaped strips, each with a width of 300 µm and an arc angle α of 180°.
[0119] The adhesive gels prepared in Examples 4-1 to 4-4 were subjected to 90° peel force tests, and the results are shown in Table 3. The peel force required when peeling from the top of the arc is different from the peel force required when peeling from the two arms of the arc strip, resulting in anisotropic peel force with an anisotropy ratio of 1.2-1.8.
[0120] Table 3
[0121]
[0122] Friction performance test
[0123] The adhesive gels prepared in Examples 4-1 to 4-4 were subjected to tribological tests to evaluate the anisotropy of their frictional forces. The test methods are as follows: Figure 4 As shown, the adhesive strips of the gel to be tested were placed with the side facing upwards. A cylindrical stainless steel probe with a diameter of 1 cm was brought into contact with the strip surface of the adhesive gel, and a pressure of 30 mN was applied. The probe was moved from the top of the arc towards the two arms, with a sliding speed of 0.1 mm / s and a sliding distance of 1 cm. The maximum force generated in the y-direction during the sliding process was recorded as the frictional force N1 from the top of the arc towards the two arms, and the maximum force generated in the y-direction during the sliding process in the opposite direction was recorded as the frictional force N2 from the two arms towards the top of the arc. The results are shown in Table 4. The frictional force from the top of the arc towards the two arms is different from the frictional force from the two arms towards the top of the arc, resulting in anisotropic frictional forces with an anisotropy ratio of 1.2-1.7.
[0124] Table 4
[0125]
[0126] Wear resistance stability
[0127] The abrasion resistance of the adhesive gels prepared in Examples 4-4 was tested using the following method: A stainless steel cylindrical probe with a diameter of 1 cm was placed on the prepared adhesive gel with adhesive strips under a pre-pressure of 1 N, and moved parallel to the adhesive gel at a speed of 1 mm / s. After 1000 reciprocating movements, the sample was freeze-dried, and the microstructure of the adhesive gel surface was observed. (See results below.) Figure 5 Optical photographs and microscopic scanning electron microscope images show that the boundary between the adhered and non-adhesive strips remains clearly visible after 1000 rubs, and the adhesion force remains at the original level, proving that the anisotropic adhesion gel has excellent friction resistance and stability.
[0128] Example 5-1
[0129] The patterned substrate preparation process is the same as in Example 1, except that the patterned substrate with alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the sharp-angled stripes is 300 µm and the angle is 45°.
[0130] The adhesive gel was prepared in the same manner as in Example 1, but it consisted of alternating adhesive and non-adhesive pointed strips. Each adhesive and non-adhesive pointed strip had a width of 300 µm and an angle... θ It is 45°.
[0131] Example 5-2
[0132] The patterned substrate preparation process is the same as in Example 5-1, except that the patterned substrate with alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the sharp-angled stripes is 300 µm and the angle is 90°.
[0133] The adhesive gel was prepared in the same manner as in Example 5-1, but it had alternating adhesive and non-adhesive pointed strips, each with a width of 300 µm and an angle of... θ It is 90°, see the diagram. Figure 6 .
[0134] Example 5-3
[0135] The patterned substrate preparation process is the same as in Example 5-1, except that the patterned substrate with alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the sharp-angled stripes is 300 µm and the angle is 135°.
[0136] The adhesive gel was prepared in the same manner as in Example 5-1, but it had alternating adhesive and non-adhesive pointed strips, each with a width of 300 µm and an angle of... θ It is 135°.
[0137] The friction performance test method is as described in Example 3-1. The maximum force generated in the y-direction during sliding is recorded as the friction force N3 from the sharp corner towards the arms, and the maximum force generated in the y-direction during sliding in the opposite direction is recorded as the friction force N4 from the arms towards the sharp corner. The results are shown in Table 5. The friction force from the sharp corner towards the arms is different from the friction force from the arms towards the sharp corner, resulting in anisotropic friction with an anisotropy ratio of 1.2-1.5.
[0138] Table 5
[0139]
[0140] Example 6-1
[0141] The patterned substrate preparation process is the same as in Example 1, except that the patterned substrate with alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the hydroxyl-modified sharp-angled stripes is 1.5 mm, and the width of the silane-modified sharp-angled stripes is 300 µm with an angle of 90°.
[0142] The adhesive gel was prepared in the same manner as in Example 1, but it consisted of alternating adhesive and non-adhesive pointed strips. Each non-adhesive pointed strip was 1.5 mm long, and each adhesive pointed strip was 300 µm wide with an angle of... θ It is 90°.
[0143] Example 6-2
[0144] The patterned substrate preparation process is the same as in Example 6-1, except that the patterned substrate with alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the hydroxyl-modified sharp-angled stripes is 2.7 mm, and the width of the silane-modified sharp-angled stripes is 300 µm with an angle of 90°.
[0145] The adhesive gel was prepared in the same manner as in Example 6-1, but with alternating adhesive and non-adhesive pointed strips. Each non-adhesive pointed strip was 2.7 mm long, and each adhesive pointed strip was 300 µm wide with an angle of... θ It is 90°.
[0146] Example 6-3
[0147] The patterned substrate preparation process is the same as in Example 6-1, except that the patterned substrate with alternating hydroxyl-modified sharp-angled stripes and silane-modified sharp-angled stripes is obtained by changing the shape of the mask. The width of the hydroxyl-modified sharp-angled stripes is 1 cm, and the width of the silane-modified sharp-angled stripes is 300 µm. θ It is 90°.
[0148] The adhesive gel was prepared in the same manner as in Example 6-1, but with alternating adhesive and non-adhesive pointed strips. Each non-adhesive pointed strip was 1 cm long, and each adhesive pointed strip was 300 µm wide and had an angle of 90°.
[0149] The adhesive gels prepared in Examples 6-1 to 6-3 were subjected to a 90° peel force test, and the results are shown in Table 6. The peel force required to peel from the pointed tip is different from the peel force required to peel from the two arms of the pointed strip, resulting in anisotropic peel force with an anisotropy ratio of 1.3-2.3.
[0150] Table 6
[0151]
[0152] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. An anisotropic adhesive gel, characterized in that: The adhesive gel is a 2D adhesive strip array composed of adhesive strips and non-adhesive strips alternatingly; Wherein, the adhesive strip is obtained by interfacial self-assembly and polymerization of a prepolymer solution rich in adhesive gel monomers in a patterned area modified with n-octyltriethoxysilane; The non-adhesive strip is obtained by interfacial self-assembly and polymerization of a prepolymer solution rich in non-adhesive gel monomers in a hydroxyl-modified patterned area; The adhesive strip and the non-adhesive strip are respectively in the shape of an arc strip or a pointed strip, and the adhesive strip and the non-adhesive strip have the same shape and the openings thereof face the same direction; When the adhesive strip and the non-adhesive strip are in the shape of arc strips, the arc range is 45-180°; When the adhesive strip and the non-adhesive strip are in the shape of pointed strips, the pointed angle ranges from 45° to 135°.
2. The adhesive gel according to claim 1, characterized in that The adhesive gel monomer is selected from one or more of isooctyl acrylate, dodecyl methacrylate, n-butyl acrylate, dopamine octyl ester, and oleic acid methacrylate; The non-adhesive gel monomer is selected from one or more of acrylamide, hydroxyethyl methacrylate, hydroxyethyl acrylate, N,N-dimethylacrylamide, methacrylamide, and N-isopropylacrylamide.
3. The adhesive gel according to claim 1, characterized in that The width of each adhesive strip and each non-adhesive strip is 10 μm-1.0 cm, respectively.
4. The adhesive gel according to claim 3, characterized in that When the adhesive strip and the non-adhesive strip are in the shape of pointed strips, the peeling strength from the pointed tip of the adhesive strip is greater than the peeling strength from the two arms of the pointed strip, and the sliding friction from the pointed tip of the adhesive strip to the two arms of the pointed strip is greater than the sliding friction from the two arms of the pointed strip to the pointed tip; When the adhesive strip and the non-adhesive strip are in the shape of arc strips, the peeling strength from the arc top of the adhesive strip is greater than the peeling strength from the arc two arms, and the sliding friction from the arc top of the adhesive strip to the arc two arms is greater than the sliding friction from the arc two arms to the arc top.
5. The adhesive gel according to claim 3, characterized in that When the adhesive strip and the non-adhesive strip are in the shape of pointed strips, the peeling force from the pointed tip of the adhesive strip is 1.3-4.0 times the peeling force from the pointed arms, and the sliding friction force from the pointed tip of the adhesive strip to the pointed arms is 1.2-3.0 times the sliding friction force from the pointed arms to the pointed tip; When the adhesive strip and the non-adhesive strip are in the shape of arc strips, the peeling force from the arc top of the adhesive strip is 1.2-5.0 times the peeling force from the arc two arms, and the sliding friction force from the arc top of the adhesive strip to the arc two arms is 1.2-3.0 times the sliding friction force from the arc two arms to the arc top.
6. The method for preparing the adhesive gel according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Preparation of patterned substrate The substrate is subjected to plasma treatment and n-octyltriethoxysilane modification treatment respectively according to a predetermined adhesive strip array pattern to obtain a patterned substrate with different modified areas arranged alternately; 2) Prepare a prepolymer solution rich in adhesive gel monomers and a prepolymer solution rich in non-adhesive gel monomers mixing an adhesion gel monomer, a first cross-linking agent, and a first photoinitiator to obtain a prepolymer solution rich in adhesion gel monomer; mixing the non-adhesive gel monomer, the second cross-linking agent and the second photoinitiator in solvent water to obtain a prepolymer solution rich in the non-adhesive gel monomer; 3) Preparation of adhesion gel A prepolymer liquid rich in adhesive gel monomers and a prepolymer liquid rich in non-adhesive gel monomers are mixed to obtain a mixed prepolymer liquid, 0.05-0.2 g of an emulsifier is added per 10 g of the mixed prepolymer liquid, and the emulsified solution is applied to a patterned substrate. The adhesive gel monomers and the non-adhesive gel monomers complete self-assembly and polymerization processes on the patterned substrate to obtain an adhesive gel.
7. The preparation method according to claim 6, characterized in that: The molar ratio of the adhesive gel monomer to the non-adhesive gel monomer in the mixed prepolymer solution is 3:1-1:
1.
8. The preparation method according to claim 6, characterized in that: In the prepolymer solution rich in adhesion gel monomer, the molar ratio of the adhesion gel monomer, the first cross-linking agent and the first photoinitiator is 0.05-0.20: 0.0010-0.0025: 0.0001-0.0002; In the prepolymer solution rich in non-adhesive gel monomer, the concentration of the non-adhesive gel monomer is 0.5-3.0 mol / L, the content of the second cross-linking agent is 0.05-0.2 mg / mL, and the content of the second photoinitiator is 0.05-0.2 mg / mL.
9. The preparation method according to claim 6, characterized in that: The first cross-linking agent is selected from one or more of triethylene glycol acrylate, diethylene glycol dimethacrylate, polyethylene glycol diacrylate, and polyethylene glycol dimethacrylate; The first photoinitiator is selected from 2-hydroxy-2-methyl-1-phenylpropanone and / or 1-phenyl-1,2-propanedione-2-acetanilide; The second cross-linking agent is selected from N,N-dimethylbisacrylamide and / or N,N'-bis(2-aminoethyl)acrylamide; The second photoinitiator is selected from one or more of α-ketoglutaric acid, Irgacure 2959, acetophenone, and benzoylbenzophenone; The emulsifier is selected from one or more of polyvinyl alcohol, Tween, sodium lauryl sulfate and lecithin.
10. Use of the adhesive gel according to any one of claims 1 to 5 in preparing flexible adhesive grippers, smart wearable devices, and wall-climbing robots.
Citation Information
Patent Citations
Preparation method and application of humidity response anisotropic composite surface
CN114989470A
Adhesive material used for imitating gecko sole adhesive arrays and preparation method thereof
CN103333495A
Gel with surface patterning, preparation method and application
CN115043969A